Comparison of selected soil chemical properties of two different mangrove forests in Sarawak - Rambok, Empi; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2010)
Problem statement: Despite few studies of forest health and environmental conditions of mangrove forest in Sarawak, the data was not sufficient to facilitate baseline data and direct comparison of mangrove forest health obtained for different location of mangrove forest in Sarawak. On this regard, determination of contemporary mangrove soil condition was essential to addressing mangrove forest for forest health, carbon storage and environmental balance. The study attempts to obtained preliminary database of mangrove forest soil chemical properties and to compare the forest health from two different mangrove forest locations. Approach: Mangrove soil samples were taken from Miri and Limbang Division of Sarawak at 0-30 cm depth. Selected soil chemical properties were determined and data obtained were analyzed using Statistical Analysis System (SAS) Version 9.2. Results: The soil acidity, total N, total P, CEC and humic acid of both locations were significantly different while in terms of total carbon and organic matter were similar. Conclusion: Regional diversity has significant effects the soil acidity, total N, total P, CEC and yield of the study areas. Data obtained can be useful for further study of carbon stock and nutrient content.